Predictive control of a series-input, parallel-output, back-to-back, flying-capacitor multilevel converter - Du Toit, Daniel Josias (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--Stellenbosch University, 2011.